Design and realization of the Questionnaire for the evaluation of teaching and the relationship with the teacher - Ostinelli, Giorgio (Swiss Journal of Educational Research, 2018)
The evaluation of teaching has always been a theme at the same time important and difficult to achieve. While a teacher continuously assesses other individuals during her/his career, it is rather common that s/he doesn’t like to be evaluated. Is it really possible to introduce forms of assessment able to be at the same time rigorous and respectful of both professionalism and personality of teachers?The development of an improvement-oriented environment inside individual schools may be a positive opportunity to give an answer to this question, and, in short, that’s exactly what happened at the Scuola Professionale e Artigianale (SPAI) of Mendrisio (Switzerland) during the last years. In fact, as part of a federal project aimed at developing experiences in the domain of school self-evaluation (DAAP) a workgroup, representative of all school’s stakeholders (teachers, students, management, etc.), developed, with the consultancy of a School Improvement Advisor/researcher (SIA), a questionnaire aimed at the assessment of both teaching and interaction between teacher and students. This article describes the steps that led to the creation of this instrument and the processes targeted at the improvement of its validity and reliability, with the scope of its use on a larger scale by Italian-speaker teachers.